Penerapan Model Pembelajaran Round Robin Brainstorming Untuk Meningkatkan Aktivitas Belajar Siswa Pada Mata Pelajaran Akidah Akhlak Kelas VII MTs Swasta Darul Arafah Pangkalan Berandan - Widya Suhaidah, Muhizar Muchtar, Zaifatur Ridha (Jurnal Pusat Studi Pendidikan Rakyat, 2023)
This study aims to determine the increase in student learning activities by learning the Round Robin Brainstorming learning model at MTs. Private Darul Arafah Pangkalan Berandan. This type of research is classroom action research. The object of this research is to increase student learning activities through the Round Robin Brainstorming learning model in class VII MTs. Private Darul Arafah Pangkalan Berandan. The research subjects were students of class VII.1, totaling 39 people. Before the action is carried out, observations are made which include giving tests and interviews to class teachers to find out the activities and student learning outcomes. The data provided was obtained from sheets from observation sheets of activities, attitudes, and student learning outcomes in the form of questions and descriptions given. The test is given twice at the end of each cycle. After being given action through the Round Robin Brainstorming learning model in class action research carried out in class VII MTs. Private Darul Arafah Pangkalan Berandan from the results of observations of student learning activities in cycle II experienced an increase compared to cycle I. The average observation in cycle I was 53.84%, the average in cycle II was 74.35%. In cycle II there was an increase in the percentage of student learning activity by 20.51% from cycle I. From the results of the pre-test before the action obtained an average value of 67.61 and the results of the post-test after the action obtained an average value of 78.23. If measured by N-gain, the average student's ability is 0.32 in the medium category. This shows that the Round Robin Brainstorming learning model according to MTs students. Private Darul Arafah Pangkalan Berandan is considered good, namely between the classification of 56-75%. Thus the application of the Round Robin Brainstorming learning model can increase student learning activities.